2*(1+ 14)7 + 6/0.5^3
= 2*15*7 + 6/ 0.125
=210 + 6000/125
= 210 + 48 = 258
The next step Juan will take is to multiply the second fraction by (x-2)/(x-2).
Given that Juan needs to rewrite this difference as one expression (3x/(x²-7x+10))-(2x/(3x-15)) and factor the denominator as (3x/(x-2)(x-5))-(2x/3(x-5)).
An algebraic expression in mathematics is an expression composed of variables and constants and algebraic operations (addition, subtraction, etc.). Expressions are made up of concepts.
The given expression is (3x/(x²-7x+10))-(2x/(3x-15))
Firstly, we will factored the denominator as
(3x/(x-2)(x-5))-(2x/3(x-5)).
Now, we will multiply and divide the second fraction by (x-2), we get
(3x/(x-2)(x-5))-((2x(x-2))/3(x-5)(x-2)).
Hence, the next step when subtracting these expressions (3x/(x-2)(x-5))-(2x/3(x-5)) is multiply the second fraction by (x-2)/(x-2).
Learn more about algebraic expression from here brainly.com/question/4344214
#SPJ4
Answer:912
Step-by-step explanation:
deltamath
Answer:
160 off 20p coins
Step-by-step explanation:
- 1 p, 20 p, 5 p coins
- 1 p= 3/8 of the bag
- 5 p= 1 p= 3/8 of the bag
20 p coins= 640 - 640*(3/8+3/8)= 640*(1- 6/8)= 640 * 2/8= 640* 1/4= 160
Yes that statement is true.